In vitro and in vivo evaluation of 3D bioprinted small-diameter vasculature with smooth muscle and endothelium. (21st October 2019) - Cui, Haitao; Zhu, Wei; Huang, Yimin; Liu, Chengyu; Yu, Zu-Xi; Nowicki, Margaret; Miao, Shida; Cheng, Yilong; Zhou, Xuan; Lee, Se-Jun; Zhou, Yifu; Wang, Suna; et al.
Abstract: The ability to fabricate perfusable, small-diameter vasculature is a foundational step toward generating human tissues/organs for clinical applications. Currently, it is highly challenging to generate vasculature integrated with smooth muscle and endothelium that replicates the complexity and functionality of natural vessels. Here, a novel method for directly printing self-standing, small-diameter vasculature with smooth muscle and endothelium is presented through combining tailored mussel-inspired bioink and unique 'fugitive-migration' tactics, and its effectiveness and advantages over other methods (i.e. traditional alginate/calcium hydrogel, post-perfusion of endothelial cells) are demonstrated. The biologically inspired, catechol-functionalized, gelatin methacrylate (GelMA/C) undergoes rapid oxidative crosslinking in situ to form an elastic hydrogel, which can be engineered with controllable mechanical strength, high cell/tissue adhesion, and excellent bio-functionalization. The results demonstrate the bioprinted vascular construct possessed numerous favorable, biomimetic characteristics such as proper biomechanics, higher tissue affinity, vascularized tissue manufacturing ability, beneficial perfusability and permeability, excellent vasculoactivity, and in vivo autonomous connection (∼2 weeks) as well as vascular remodeling (∼6 weeks). The advanced achievements in creating biomimetic, functional vasculature illustrate significant potential toward generating a complicated vascularized tissue/organ for clinical transplantation.